Numerical Analysis of Time-Accurate Solution of Nonlinear Flow Models by Implicit Finite Differences - Dey, S. K. (Nonlinear Analysis: Modelling and Control, 2003)
Implicit finite differences are often applied to solve flow models. A standard technique to solve these equations is Newton's method. lf time step is too large although the difference equation could be computationally stable, Newton's method may fail, and PFI (perturbed functional iterations) may be fruitful. This is discussed in this article applying nonlinear D-mapping analysis.
Keywords: nonlinear flow; finite differences; perturbed functional iterations